Pediatric urology a general urologist's guide - Palmer, Jeffrey S. (Springer eBooks., 2011)
A vast number of children in the United States are evaluated and treated for urologic conditions by urologists practicing general urology due to the relatively few fellowship-trained pediatric urologists. Pediatric Urology: A General Urologist?s Guide is written specifically for general urologists as a concise and comprehensive reference of the more common pediatric urologic conditions. Other health practitioners (i.e. pediatrician, family practitioner, residents, medical students, and mid-level providers) will also find this book a key reference. Written by well-respected pediatric urologists, this volume will assist the health care provider to rapidly review the essential aspects of the physical examination, evaluation, diagnostic testing, and management while the patient is still in the office. The chapters are arranged into four sections to allow for easier access to the information: office urology, genitalia, urinary tract, and miscellaneous topics. Furthermore, the first chapter of the book will be dedicated to facts and figures (ex. normal penile and renal lengths based on age, dosing of common medications, and grading system for vesicoureteral reflux) that serves as a single source for this information. Pediatric Urology: A General Urologist?s Guide offers the reader the essential information to assist them in the care of children.